Application of material flow analysis and water quality modelling to facilitate the efficiency of leachate management system / Tengku Nilam Baizura Tengku Ibrahim - Tengku Nilam Baizura , Tengku Ibrahim (2021)
Leachate from landfills is known to be one of the major environmental impacts, particularly those constructed near rivers. Therefore, this study is conducted to assess the impact of discharged leachate, using SL Landfill and Sembilang River as the case study. Solid waste generated from 2015-2016 served as input data on volume and composition of the solid waste that was sent to SL Landfill. A material flow analysis (MFA) is employed to trace the fate of solid waste that has been disposed and leachate that is produced at SL Landfill using STAN software. Six parameters in Water Quality Index (WQI), viz. DO, pH, BOD, COD, NH3N, TSS were used to define the quality of the river water. A total of 80 water samples were collected monthly for 1 year from 10 sampling stations. In order to predict and assess the pollutant transport in Sembilang River basin, QUAL2K was used as a simulation model. Water quality parameters (DO, BOD and NH3-N) were chosen to model the impact from the SL landfill effluent towards Sembilang River. The findings showed that the highest composition of waste that was present at the landfill can be categorized as food waste with 32% of the total waste input. Results from the MFA model showed that the amount of leachate generated from SL landfill was 123,386 m3/year. The finding had also successfully identified the input and output flow of SL Landfill, with an overall input values of 948,505 ton per year and the output at 393,292 ton per year. From 3 different possible scenarios that were chosen, results from the MFA showed that composting was the most effective method in terms of reducing leachate production in SL Landfill which expected to reduce leachate production by up to 92%. The Sembilang River water quality results show that it falls in Class III of the WQI, which ranges from 43.46 to 68.03 mg/L. Different water quality model scenarios were simulated in order to assess the pollutant transport on the Sembilang River water quality and it was found that the effects of different scenarios for water quality parameters were particularly noticeable for DO and BOD. However, for the NH3N parameters there were no significant change and had remained in Class IV and V. This was due to the high NH3N concentration from a few points along the river. These findings showed that the MFA, water quality assessment and modeling were found to be the best methods to predict and analyzed the composition of waste to the leachate production and the effect to the river water pollution.